Nutrition for pregnant women and nursing mothers in the perinatal center: subjective and objective assessments - E. N. Berezkina; V. P. Novikova; A. N. Zavyalova; A. V. Gostimsky; A. M. Susanina; O. V. Lisovsky; E. A. Turganova (Лечащий Врач, 2021)
Nutrition of pregnant and nursing women in the hospital requires more careful attitude and, possibly, revision and addition of existing recommendations. Analysis of nutrition in the obstetric physiological department revealed a discrepancy between actual nutrition and requirements for basic nutrients and energy for pregnant women, with a diet deficiency in certain nutrients (vitamin D, iodine, zinc, and iron) with normal energy, protein, fat and carbohydrate content and excess in a number of other nutrients (phosphorus, potassium, sodium, vitamins C and B12).